KONTRIBUSI EFEKTIVITAS MANAJEMEN EKSTRAKURIKULER TERHADAP PRESTASI SEKOLAH NON AKADEMIK - Astafiyah Astafiyah (Tarbawi, 2018)
The objectives of this study are (1) to describe the level of extractive management effectiveness in Serang Junior High School 18; (2) to describe how much non-academic school achievement; (3) describes how much extracurricular non-academic school achievements. The research method used in this study is a quantitative method, with a correlational approach. The population in this study were students who took extracurricular activities as many as 120 students, thus the study sample was 30 respondents. The data collection techniques used a questionnaire. The conclutions of the research results are (1) the level of extracurricular management effectiveness at Serang Junior High School 18 is classified as good with 59.19%; (2) the level achievement of non-academic schools in Serang Junior High School is classified as good with 63.41%; and (3) the contributions of the effectiveness of extracurricular management variables on the achievement of non-academic school at 38.44%. Keywords. Effectiveness, extracurricular management, non-academic achievements.